Strategic Planning and Public Sector Effectiveness in Jordan: A Conceptual Approach - et. al., Shuroog Hassan Ali Obeidat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strategic planning has recently become more widely accepted in recent theorization, and it has been seen as a physical, social, emotional, even spiritual and complex human activity. Thus, the aim of this study is to investigate the correlations between some selected strategic planning practices and organizational effectiveness in public sector of Jordan. The study will approach this conceptual research by reviewing the relevant past studies pertaining to strategic planning process, affective commitment and organizational effectiveness in Jordan. Additionally, this study is examining the important dimensions of strategic planning practices that are considered crucial in a situation where organization is facing global, complex and highly turbulent external environment. Those measuring practices are horizon of planning, locus of planning, flexibility of planning and environmental scanning intensity while being mediated respectively by affective commitment with their relationships with organizational effectiveness. The Herzberg’s Two-Factor Theory as an underpinning theory shows that the overall connection of these variables determines how an individual’s behaviour is affected or altered by individual-work place relationship which include the economic and social environment, technology and the pace of environmental change.